4. Does small fiber pathology in PD change over time?. Issue 12 (December 2017) - Nolano, M.; Provitera, V.; Stancanelli, A.; Saltalamacchia, A.; Caporaso, G.; Lullo, F.; Borreca, I.; Piscosquito, G.; Lanzillo, B.; Santoro, L.
Abstract : Small fiber pathology is part of the clinical picture of PD. Cross-sectional studies have shown no correlation between intraepidermal nerve fiber (IENF) density and patient disease duration and severity. However, it is not known whether IENF density changes over time. We aimed to assess the progression of small fiber pathology in PD patients along the disease course. We assessed epidermal innervation at time 0 and after 1–9 years (mean 3.5) in 17 PD patients (M/F = 11/6, age = 64.4 ± 15.3) leg on punch biopsies. Patients were assessed in a rehabilitative setting. They underwent yearly 30-days hospitalizations and were trained to continue a home-personalized program of physical exercises between successive evaluations. Quantitative sensory testing and sudomotor assessment were also performed. Overall, no difference ( p  = 0.12) between the first and the last IENF density (8.7 ± 4.0 vs. 10.3 ± 4.9) assessment was found. However, the IENF density variation correlated with the disease duration ( r  = 0.71; p  < 0.01). In fact, while in patients with shorter disease duration IENF density increased over time, in patients with longer disease duration (approximately over 8 years) an IENF loss was observed. The small fiber pathology associated to PD can improve to some extent by optimizing patient care, at least in the first stages of disease.